Job Design, Compensation and Commitment of Employee in Service Sector Organizations of Nepal - Pradhan, Gopal Man (Management Dynamics, 2020)
This study is based on the impact of Job design and Compensation system on employee commitment of service sectors of Nepal. The variables job design and compensation system are taken as independent variables whereas employee commitment is dependent variable. In this research work it is found that job design and compensation system have positive correlation with employee commitment. However, while analyzing the beta coefficient, it is found that sensitivity to job design is high followed by compensation system for employee commitment. It means that if Nepalese service sector invests a significant amount and effort for development of proper job design and to develop proper compensation system, they can improve employee commitment for accomplishment of assigned job in an effective way.